Role of the nuclear membrane protein Emerin in front-rear polarity of the nucleus - Paulina Nastały (Nature Portfolio, 2020)
During cell migration, cells are polarized with distinct front vs. rear regions but whether and how polarity is transmitted to the nucleus is unclear. Here the authors show that frontally-biased endoplasmic reticulum and the nuclear membrane protein Emerin contribute to front-rear nuclear cell polarity.